Economic-Based Food Waste Management Strategy (Qualitative Study at Elang Medika Corpora/EMC Alam Sutera Hospital in South Tangerang) - Seputra, Hawreyvian Rianda; Rohendi, A.; Efawati, Yen (CV. Civiliza Publishing, 2025)
This study aims to analyze the implementation of food waste management at EMC Alam Sutera Hospital, assess its impact on the environment and hospital operations, and identify strategies for utilizing it to increase economic value. The approach used is qualitative with descriptive research type. Data were collected through interviews, observations, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing. The results showed that food waste management at EMC Alam Sutera Hospital is carried out through sorting organic waste, processing it into compost, and distributing the processed products for use in the hospital area or for sale to the surrounding community. This strategy has a positive impact on the environment by reducing the volume of waste disposed to landfills and increasing operational efficiency through reduced waste disposal costs. In addition, the utilization of food waste as compost provides economic opportunities for the hospital by making it an additional source of income while supporting the circular economy principle.